2014
DOI: 10.1121/1.4900568
|View full text |Cite
|
Sign up to set email alerts
|

Auditory sensitivity of seals and sea lions in complex listening scenarios

Abstract: Standard audiometric data, such as audiograms and critical ratios, are often used to inform marine mammal noise-exposure criteria. However, these measurements are obtained using simple, artificial stimuli-i.e., pure tones and flat-spectrum noise-while natural sounds typically have more complex structure. In this study, detection thresholds for complex signals were measured in (I) quiet and (II) masked conditions for one California sea lion (Zalophus californianus) and one harbor seal (Phoca vitulina). In Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…deer, elk) (Lingle and Riede, 2014) and even aquatic mammals such as pinnipeds (e.g. walruses, seals) (Cunningham et al, 2014; Reichmuth and Casey, 2014). Note, however, that some emotional calls, especially distress vocalizations, appear to reflect evolutionary conserved mechanisms underlying both production and behavioral responses (Lingle et al, 2012).…”
Section: Bottom-up Perspectives Of Vision and Hearing Modelsmentioning
confidence: 99%
“…deer, elk) (Lingle and Riede, 2014) and even aquatic mammals such as pinnipeds (e.g. walruses, seals) (Cunningham et al, 2014; Reichmuth and Casey, 2014). Note, however, that some emotional calls, especially distress vocalizations, appear to reflect evolutionary conserved mechanisms underlying both production and behavioral responses (Lingle et al, 2012).…”
Section: Bottom-up Perspectives Of Vision and Hearing Modelsmentioning
confidence: 99%
“…Furthermore, conventional methods for predicting masking are often based on average noise levels over the duration of the target signal, which may not be appropriate for noises that vary significantly in time. Prior work has shown that the classic application of critical ratio data to predict masking in realistic listening scenarios is valid in some cases and inaccurate in others (see, e.g., Erbe and Farmer, 2000;Erbe, 2002;Jensen et al, 2009;Branstetter et al, 2013;Dooling et al, 2013;Cunningham et al, 2014). The extent to which this conventional method can be reasonably applied to evaluate hearing in marine mammals in the presence of impulsive noise remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Calculations were carried out for 125Hz since it is one of two 1/3-octave bands (63 and 125Hz) proposed to be monitored by MSFD and is believed to be within the hearing range of pinnipeds such as grey seals (Kastak & Schusterman, 1998;Cunningham et al, 2014).…”
Section: Transmission Loss Over Transect Amentioning
confidence: 99%